THE IMPACT OF SELF-OPERATED FINANCING INDICATORS ON MARKET CAPITALIZATION-RESEARCH ON SELECTED BANKS IN THE IRAQI BANKING SECTOR - Researcher: Youssef Hassan Ali; Prof. Dr. Ibrahim Ali Kurdi (Galaxy International Interdisciplinary Research Journal, 2024)
The study aims to demonstrate the impact of the relationship between self-financing indicators and market value added. The study uses a sample of Iraqi banks listed on the Iraqi Stock Exchange between 2014 and 2023 (10). Real estate financing indicators are measured through capital adequacy and debt ratios to measure the studied variables. The increase in market value is measured by the market value of new property rights minus the book value of equity. In statistical analysis, correlation and regression coefficients are used to test research hypotheses, determine the magnitude of correlation and influence, study the significance level between variables, and use statistics programs (SPSS) and (AMOS). There is a negative (inverse) moral link between the self-financing indicator (indexed as equity to total assets) and market residual value, which means that the ratio of equity to total assets will increase accordingly. There is a positive moral correlation (direct) between the financing ownership indicator (according to the debt ratio indicator) and the market value increase through the decrease in market residual value. This means the debt level ratio will increase as the market value decreases. Add to. The study suggests that bank management must pay attention to the relationship between financing needs and the bank’s market capitalization and determine the bank’s capital needs by measuring the bank’s financing needs.